The Concept of Fairness Accounting and its Role in Reducing Earnings Management Practices - عبد الله, سلمان حسين; توفيق, عدالت محمد (Journal of Economics and Administrative Sciences, 2012)
The aims of research is diagnose and indicate the role of fairness in the work of accounting, which is important in reducing the unacceptable practices to manage earnings by economic units, As well as the interpretation and indicate Ethical inside in the accounting and accountants in particular practices in the area of ​​earnings management to reduce the negative effects of the practice and display the results mentioned acts according to what is supposed to be for the purposes of service users, Researchers have identified that one hypothesis, that "Fairness of accountants in of their work accounting lead to a reduction of earnings management practices". The results suggest that the accounting practices that lead to the manipulation of accounting results for the purpose of creating a different impression of the real economic performance of the corporation accounting practices are immoral of the company's accounting practices are unethical, Achieving that fairness in the work of accounting leads to reduction of such practices is not ethical, This result is achieved hypothesis, As well as the fairness commitment of accountants in the accounting work will reduce the risk of exposure to the risk of corporate bankruptcy or collapse, The researchers recommends the need to introduce the subject of accounting ethics and the philosophy of ethics as a separate vocabulary within the curricula of the accounting department at Iraqi universities.